Paternal psychosocial work conditions and mental health outcomes: A case-control study - Hershler Ruth; Dunn James; Tansey James; Ostry Aleck; Maggi Stefania; Chen Lisa; Hertzman Clyde (BMC, 2008)
Abstract Background The role of social and family environments in the development of mental health problems among children and youth has been widely investigated. However, the degree to which parental working conditions may impact on developmental psychopathology has not been thoroughly studied. Methods We conducted a case-control study of several mental health outcomes of 19,833 children of sawmill workers and their association with parental work stress, parental socio-demographic characteristics, and paternal mental health. Results Multivariate analysis conducted with four distinct age groups (children, adolescents, young adults, and adults) revealed that anxiety based and depressive disorders were associated with paternal work stress in all age groups and that work stress was more strongly associated with alcohol and drug related disorders in adulthood than it was in adolescence and young adulthood. Conclusion This study provides support to the tenet that being exposed to paternal work stress during childhood can have long lasting effects on the mental health of individuals.